Blood Flows in Tributaries of the Portal Vein: Anatomical and Angiographic Studies in Normal Beagle Dogs. (7th November 2014) - Mogicato, G.; Vautravers, G.; Meynaud‐Collard, P.; Deviers, A.; Sautet, J.
Summary Liver anatomy, particularly its vascularization, has been investigated in many studies in dogs. Knowledge of blood flow from the main tributaries of the portal vein (PV) is necessary to explain the preferential sites of secondary lesions within the liver based on the site of the initial malignant lesion. How these flows come together was established in an earlier ex vivo study. Here, we highlight in vivo the blood flows from the main PV tributaries and their distribution in the liver of normal dogs. Portographs of the main PV tributaries were obtained in seven dogs after injection of an angiographic contrast medium. After euthanasia, the livers and their portal vascularization (PV and tributaries) were extracted for a comparative corrosion cast study. Flows were demonstrated in the cranial mesenteric vein, caudal mesenteric vein and splenic vein. However, no proper flow could be distinguished for the gastroduodenal and ileocolic veins. All these tributaries primarily supply the lateral liver lobes (right or left). Most of our observations indicate that the cranial mesenteric, caudal mesenteric and splenic veins primarily supply the right lateral lobe and the caudate process of the caudate lobe and secondarily the left lateral lobe, left medial lobe and the quadrate lobe. The two other tributaries (gastroduodenal and ileocolic veins) primarily supply the right lateral lobe and the caudate process of the caudate lobe.